Application of transthoracic echocardiography to assess the dynamic evolution of early cardiac damage induced by abdominal aorta-inferior vena cava fistula in female rats with chronic renal failure - Yiran Zhang; Lizhou Wu; Liming Liang; Kuan Li; Xianglei Kong; Haiyan Wang (PLoS ONE, 2025)
Objective Left ventricular dysfunction (LVD) frequently occurs in patients with chronic renal failure (CRF) who have an arteriovenous fistula (AVF). In a rat model of CRF with AVF, we assessed the utility of transthoracic echocardiography for the early detection of LVD and examined the associated pathological damage. Methods Forty female rats that had successfully established a CRF model were divided into three groups: the CRF group (n = 13), the sham group (n = 13), and the AVF group (n = 14). The AVF was established (labeled as T0). Renal function and myocardial enzyme parameters were measured at T0, the 4th week (labeled as T1), and the 6th week (labeled as T2). The parameters of echocardiography were measured with an animal ultrasound device (Vevo 3100). The early diastolic peak flow velocity (E) was divided by the mitral valve’s E wave deceleration time (DT), to calculate the E/DT ratio. TOMTEC image analysis software was utilized to analyze the LV’s global longitudinal strain (GLS) and global circumferential strain (GCS). At each time point, three rats from each group were euthanized, and the left ventricular pathological tissues were collected for HE and Masson staining. Results (1) At T1, the AVF group had no significant difference in GLS, although GCS and the E/DT ratio increased. At T2, the AVF showed lower GLS and GCS and a higher E/DT ratio. (2) Significant alterations were observed in AVF group tissues stained with HE and Masson at T1 and T2. Conclusions This study found that pathological damage to the left ventricular myocardium persisted after the rat model was established. Unlike traditional echocardiography measurements, GLS, GCS, and the E/DT ratio can detect dynamic changes in left ventricular function.